2015
DOI: 10.1177/014556131509400216
|View full text |Cite
|
Sign up to set email alerts
|

Basaloid Squamous Cell Carcinoma of the Sinonasal Tract with Metastasis to the Liver: A Case Report and Literature Review

Abstract: Basaloid squamous cell carcinoma (BSCC) is a rare subtype of squamous cell carcinoma. To date, only 95 cases of sinonasal BSCC have been reported in the English-language literature, and they account for 5% of all cases of head and neck BSCC. We describe what we believe is only the second reported case of a sinonasal tract BSCC that metastasized to the liver. The patient was a 36-year-old woman who presented with right-sided nasal obstruction and a foul-smelling discharge. Clinical examination and imaging ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…BSCC occurs most frequently in the head and neck region, with a predilection for the larynx, hypopharynx, tonsil, and base of the tongue [2]. In contrast, BSCC of the sinonasal tract is uncommon, accounting for only 5% of all cases of head and neck BSCC [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BSCC occurs most frequently in the head and neck region, with a predilection for the larynx, hypopharynx, tonsil, and base of the tongue [2]. In contrast, BSCC of the sinonasal tract is uncommon, accounting for only 5% of all cases of head and neck BSCC [3].…”
Section: Discussionmentioning
confidence: 99%
“…In 1986, Wain et al [1] first reported that the histopathological characteristics of BSCC are distinct and specific. Since the first report, only 65 cases of BSCC of the nasal cavity or paranasal cavity have been reported in the English literature identified through a PubMed search [2][3][4][5][6][7][8][9]. Various treatment modalities have been reported, including surgery supplemented with postoperative radiotherapy/adjuvant chemotherapy [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation